Use of secondary data analyses in research: Pros and Cons - LL Pederson; E Vingilis; CM Wickens; J Koval; RE Mann (Journal of Addiction Medicine and Therapeutic Science - Peertechz Publications, 2020)
What are secondary data?  Secondary data refer to data that are collected by someone other than the user or are used for an additional purpose than the original one. A wide range of sources can be used as secondary data:  censuses, information collected by government departments, organizational records and data that were originally collected for other research purposes  [1-3]. Yee and Niemeier [4] discuss the benefits of longitudinal data as compared to repeated cross-sectional information.